IMPLEMENTASI PERDA KABUPATEN GOWA NO. 6 TAHUN 2016 TENTANG PENGELOLAAN PASAR TRADISIONAL PERSPEKTIF SIYASAH SYAR’IYYAH - Latifah, Humairah; Amir, Rahma (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
This article aims to find out how the management of traditional markets and the role of the Gowa Regency Government in the empowerment of sungguminasa traditional markets. This research is qualitative research with a syar'i approach, normative and sociological juridical. The results showed that the management of traditional markets by the Gowa Regency Government has been carried out in accordance with the provisions stipulated in the Perda, such as kiosk and los licensing, SIML ownership, SIMK and merchant cards. The role of the government in the empowerment of sungguminasa traditional markets is quite maximal, including coaching to traders, providing subsidies, market development and business actors. Basically, traders appreciate the management that has been done by the government, it's just that there are things that need to be improved including the maintenance of public facilities. In the Islamic constitutional system, every citizen is obliged to obey every rule issued by authoritative institutions for the sake of mutual benefit, but the facts on the ground show that there are still traders who are ignorant of the applicable provisions.